Impact of Psychological Capital on Well-Being of Social Workers: A Mixed-Methods Investigation. - Ho, Henry C Y; Chan, Ying Chuen (Social Work, 2022)
Social workers are often faced with long working hours, high job demands, and poor work–life balance, which can have detrimental effects on their well-being. It is therefore important to identify the protective factors that enable social workers to flourish and thrive. Psychological capital (PsyCap) is conceptualized as a higher-order core construct that encompasses hope, efficacy, resilience, and optimism. This study aims to investigate the impact of PsyCap on social workers' well-being and explore the underlying mechanisms of this relationship. It expands the literature by adopting a multifaceted model of well-being, accounting for the temporal order of variables, including a qualitative component, and examining the effects of PsyCap in an at-risk occupation. A two-wave prospective survey with a three-month interval was conducted with a sample of 400 full-time social workers in Hong Kong, followed by individual in-depth interviews. The quantitative results showed that PsyCap was positively associated with job satisfaction and positive affect, and negatively associated with negative affect and psychological and physical distress. The qualitative results showed that the components of PsyCap share problem-focused processes with cognitive, conative, and affective functions. The theoretical and practical implications are discussed in relation to the social services industry.